Experimental observation of chaotic hysteresis in Chua's circuit driven by slow voltage forcing. (January 2023) - Gomes, Iacyel; Korneta, Wojciech; Stavrinides, Stavros G.; Picos, Rodrigo; Chua, Leon O.
Abstract: The Chua's circuit has been considered as a paradigm for the investigation of chaos, but it still presents many unexplored dynamics. Chaotic hysteresis is an effect observed when the hysteresis phenomenon and chaotic dynamics phenomenon act simultaneously. It is an interesting phenomenon since it is observed in a variety of disciplines, and it has been utilized in explaining the mechanism of bursting oscillations, rich dynamics in thermal convection, and economic financial crisis, to mention a few. In this paper, we report the experimental observation of chaotic hysteresis in a Chua's electronic circuit driven by both a dc and a slow triangular voltage source. One and two hysteresis loops were observed in single and double scroll chaotic regimes, respectively. We present variations of the attractor that are induced by voltage changes, as well as the dependence of the hysteresis effect on both the driving frequency and the distance from the threshold passing from single to double-scroll chaotic regimes. Our results help in expanding our knowledge on unexplored dynamics of Chua's circuit as well as contribute to chaos control theory with a potential for applications. Highlights: Experimental observation of chaotic hysteresis in a Chua's circuit The circuit was driven by both a DC and a slow triangular voltage source. One and two hysteresis loops are observed. The variations of the dynamic attractor due to voltage changes are presented and characterized.